Managing Intertextuality in Ennodius’ Corpus: The Case of 1V. (= dict. 1H.) Dictio Ennodi diaconi in natale Laurenti Mediolanensis episcopi - Cofano, Martina (Sapiens ubique civis, 2023)
‘There is too much literature between reality and him’, said Labriolle: this seems such an adequate statement for Ennodius‘ corpus, since it is normal to stumble upon references or quotations by other authors, either pagan or Christian ones. This paper takes into account Ennodius 1V. (= dict. 1H.) as a case study and aims at examining in detail which works and authors Ennodius uses in order to arrange one dedication. The declamation has been divided in five thematic sections; each shows a different percentage of intertextual categories such as clear reference, self-quotation, altered reference and word collocation. Through statistical evidence, the author of this paper has thought back on Ennodius‘ overall technique in making rhetorics: a good way of paying homage to the summi and the minores, or the easiest way to bundle up quotes and so to earn an entire piece of literature?